Economic operation of islanded micro-grids via modified active disturbance rejection control - Wu, Zhenlong; Liu, Yanhong; Chen, Pengchong; Chen, YangQuan (International journal of electrical power & energy systems, 2024)
The islanded micro-grid is playing a more and more significant role to absorb more wind and solar energy because of its advantages such as flexibility, cleanliness and environmental friendliness. However, the randomness and transient of renewable energy result in many challenges for the economic operation of the islanded micro-grid. The load frequency control is the core influencing factor for the economic operation. A modified active disturbance rejection control (MADRC), combined with a compensation part and an amplitude limiter, is proposed for the load frequency control with high-proportional renewable energy. The convergence of the extended state observer is analyzed theoretically. Then a pragmatic tuning procedure is provided by examining the influence of MADRC’s parameters on the control performance. Finally, the proposed control strategy is applied to the load frequency control of the islanded micro-grid and simulations under different conditions are carried out. The simulation results compared with other comparative controller strategies show that MADRC can obtain the best control performance with good robustness. Quantitative data demonstrates the improvement of the proposed method in terms of economic operation and the proposed method also shows promising engineering application potential. •A MADRC scheme is restructured for the load frequency control to enhance the economic operation of the islanded micro-grid.•The convergence of the proposed extended state observer is analyzed theoretically.•A pragmatic tuning procedure is provided for MADRC.•The effectiveness of the proposed MADRC is illustrated under different conditions.